Pengaruh Pengetahuan Investasi, Resiko Dan Return Terhadap Keputusan Investasi Pada Investor Pasar Modal di Nusa Tenggara Barat (Studi pada investor pasar modal di Nusa tenggara barat) - Nurfitasari; Hudaya, Robith (Fakultas Ekonomi dan Bisnis Unram, 2025)
This study aims to analyze the influence of investment knowledge, risk knowledge and return knowledge. The population in this study were capital market investors in West Nusa Tenggara, with a sample in this study totaling 399 respondents dominated by students in West Nusa Tenggara. The sampling technique used was purposive sampling. The analysis method used in this study was SEM with the SmartPLS 4.0 application. The results of the study showed that investment knowledge had a positive and significant effect on investment decisions, risk knowledge had a positive and significant effect on investment decisions, return knowledge had a positive and significant effect on investment decisions on capital market investors in West Nusa Tenggara. The results of this study are expected to be a supporter or reference for universities because universities play a role in shaping the character of investors in students through investment materials obtained in lectures, so that students will have a confident mentality to start investing.